A Markerless Augmented Reality Application for Training Upper Limb Amputees - Lima, Giogo Aparecido Cavalcante de; Lamounier Junior, Edgard Afonso; Melo, Bruno Guilherme Resende Vaz de; Soares, Alcimar Barbosa; Silva, Alexandre Carvalho; Cardoso, Alexandre (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.227935, 2022)
Amputation is a traumatic process where the person needs to start rehabilitation immediately to regain physical independence. Traditionally, rehabilitation periods last up to 12 months and have dropout rates above 35%. Initiatives to train amputees through Augmented Reality (AR) can provide more realistic and immersive experiences. This project presents a Markerless RA application for the rehabilitation of upper limb amputees. The Cylindrical Socket tracking happens in real-time through the VIVE Tracker. The application is evolving excitingly.